Effect of Motivation and Discipline Learning Student to Study Result in Social Study Social Subjects at Class VII in SMP Negeri 1 Dua Koto Kabupaten Pasaman - RAHMADIA, FAMELA; Drs. Dasrizal, MP, Drs. Dasrizal, MP; Prari Keslan, Rozana Eka (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This study aims to determine the Effect of Motivation and Discipline Learning Student to Study Result in Grade Integrated Social Subjects at Class VII in SMP Negeri 1 Dua Koto Kabupaten Pasaman. This research is a descriptive correlational. Population in this study were all students of class VII in SMP N 1 Dua Koto as consisting of four local VII.1, VII.2, VII.3, VII.4 totaling 104 students. Samples were taken with a sampling technique with a proportion of 50 % for each class so that the sample den responses amounted to 51 students. The results of the study found that : 1) There influence motivation to learning study result in social integrated studies SMP Negeri 1 Dua Koto because tcount > t table ( 3,134 > 2,00, strength of the relationship (r = 0,409) and contribution of learning motivation on learning study result in social integrated studies at SMP Negeri 1 Dua Koto Kabupaten Pasaman including very small (16,7%), (2) There is a disciplinary effect on learning outcomes in social integrated studies at SMP Negeri 1 Dua Koto Kabupaten Pasaman because of tcount > t table ( 2,833 > 2,000), there are low relationship (r = 0,357), the contribution to the discipline of the student learning study result in social studies at SMP Negeri 1 Integrated Koto Kabupaten Pasaman including two very small (14,1%) and (3) the influence significantly between learning motivation and discipline together to learn the results of Social Integrated Science subjects in SMP Negeri 1 Dua Koto Kabupaten Pasaman because of Fcount > F table (7,025 > 3,191). The are strength relationship between the two variables with learning study result in social Integrated studies at SMP Negeri 1 Dua Koto Kabupaten Pasaman including medium category (r = 0,477), whereas the contribution is small (22,8%). This suggests that the students learning motivation and discipline are the factors that determine learning study result in social integrated studies SMP Negeri 1 Dua Koto Kabupaten Pasaman.Â